Diagnostic accuracy of composite autonomic symptom scale 31 (COMPASS-31) in early detection of autonomic dysfunction in type 2 diabetes mellitus - Singh R; Arbaz M; Rai NK; Joshi R (Diabetes, Metabolic Syndrome and Obesity, 2019)
Ruchi Singh,1 Mohammed Arbaz,2 Nirendra Kumar Rai,3 Rajnish Joshi4 1Department of Physiology, All India Institute of Medical Sciences Bhopal Madhya Pradesh, Bhopal, India; 2All India Institute of Medical Sciences Bhopal, Bhopal, Madhya Pradesh, India; 3Department of Neurology, All India Institute of Medical Sciences Bhopal Madhya Pradesh, Bhopal, India; 4Department of Medicine, All India Institute of Medical Sciences Bhopal Madhya Pradesh, Bhopal, IndiaCorrespondence: Ruchi SinghDepartment of Physiology, All India Institute of Medical Sciences Bhopal, 4th Floor, Medical College Building, Bhopal 462020, Madhya Pradesh, IndiaTel +91 777 301 0095Email singhruchi00@gmail.comPurpose: Diabetic autonomic neuropathy (DAN) is a common and disabling complication of diabetes, with cardiac autonomic neuropathy (CAN) being a major cause of mortality and morbidity. Standard autonomic function tests (AFT) are cumbersome and time consuming to conduct in OPD setting.Objective: To evaluate the diagnostic accuracy of composite autonomic symptom scale 31 (COMPASS-31) as a screening test for DAN.Patients and methods: A cross-sectional study which enrolled 60 type 2 diabetes individuals was conducted at a tertiary care center. Autonomic functions were evaluated by COMPASS-31 questionnaire as well as by standard Ewing’s battery of tests; short-term heart rate variability; sympathetic skin response along with nerve conduction studies.Results: Thirty males and 24 females completed the study. Forty-nine (89%) participants had CAN, of which, 9 (17%) had definite CAN. Peripheral neuropathy was present in 20 (37%). COMPASS-31 scores showed no difference between “No CAN” and “Early CAN”. “Definite CAN” individuals differed significantly from “No and Early CAN” on COMPASS-31 scores and its gastrointestinal sub-domain. Receiver operating characteristic between “Definite CAN” and “No and Early CAN” showed fair accuracy with AUC of 0.731 (95% CI 0.561–0.901), sensitivity 77.8%, specificity 71.7% at a cut-off of 28.67 of COMPASS-31 score. Gastrointestinal sub-domain, at a cut-off score of 5.8, had 77.8% sensitivity, 60% specificity, and AUC was 0.748 (95% CI 0.603–0.894).Conclusion: COMPASS-31, a self-administered tool, requiring less time, qualifies as an acceptable screening tool, especially for definite CAN. However, individuals scoring low on COMPASS-31 are still required to be evaluated by Ewing’s battery to differentiate between “Early CAN” and “No CAN”.Keywords: autonomic neuropathy, cardiac autonomic neuropathy, autonomic function tests, heart rate variability